Preparation of a jam endemic amazonian fruits and its sensory evaluation - Luis A. Taramona-Ruiz (2025)
The aim of this study was to produce a jam from endemic Amazonian fruits and evaluate its sensory attributes. The research was experimental, applying a completely randomized block design (DBCA) with seven treatments. The fruit trees were ungurahui, (Oenocarpus bataua var. Bataua), tumbo (Passiflora mollisima) and guava (Psidium guajava L.). Sensory evaluation was carried out using a nine-point hedonic scale. Chemical-proximal analysis and dietary fiber, physicochemical and microbiological tests of the selected formulation were carried out. ANOVA and Fisher were applied to verify a significant difference between the formulations and the Friedman test to determine preference with a statistical significance level p:<0.05. The F1 (100 % ungurahui), F2 (100 % tumbo); F3 (100 % guava), F4 (50 % ungurahui and 50 % tumbo), F5 (50 % ungurahui and 50 % guava), F6 (50 % tumbo and 50 % guava) and F7 (25 % ungurahui, 50 % tumbo and 25 % guava). There was a significant difference in the attributes odor, texture, and appearance. F7 (sample 978) was the most widely accepted, which presented soluble solids (66.8°Brix) and pH 3.2; the number of yeasts and molds was < 10 estimated. F7 complies with national and international regulations, as it is a safe product of nutritional quality.